2002
DOI: 10.1176/appi.ps.53.12.1623
|View full text |Cite
|
Sign up to set email alerts
|

Medical Disorders Among Patients Admitted to a Public-Sector Psychiatric Inpatient Unit

Abstract: Active and important physical disorders are common among public-sector psychiatric patients and are frequently undetected. A total of 289 patients who were consecutively admitted to a public psychiatric hospital were screened for physical disorders and given medical evaluations when screening results suggested an active and important physical disorder. Twenty-nine percent of the patients had such disorders. Of the 119 disorders detected, 24 (20 percent) were newly diagnosed for 23 patients (8 percent). Physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 9 publications
0
17
0
2
Order By: Relevance
“…Various studies involving the thorough medical evaluation of psychiatric patients have revealed significant rates of physical disease, much of which was previously undetected (Koran et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies involving the thorough medical evaluation of psychiatric patients have revealed significant rates of physical disease, much of which was previously undetected (Koran et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although, previous research carried out in different clinical settings have documented rates of concurrent psychiatric or medical disorders in psychiatric patients (Dixon et al 1999;Zimmerman and Mattia 2000;Koran et al 2002;Evans and Charney 2003;Lambert et al 2003;Pierce and Wilson 2004;Sokal et al 2004;Kessler et al 2005;Khan et al 2005;Chwastiak et al 2006), less clinical information are available about those patients requiring long-term residential care.…”
Section: Introductionmentioning
confidence: 99%
“…Bei stationären Patienten einer staatlichen Akutstation wurde bei 9% von aufeinander folgenden Aufnahmen die Diagnose einer AS gestellt [21]. Allerdings gibt es nur wenige, qualitativ hochwertige Studien über die Diagnose AS bei stationären oder ambulanten psychiatrischen Patienten.…”
Section: Psychosom Konsiliarpsychiatr 2 2008unclassified